Dissecting major depression: The role of blood biomarkers and adverse childhood experiences in distinguishing clinical subgroups - Lo Iacono, Luisa; Bussone, Silvia; Andolina, Diego; Tambelli, Renata; Troisi, Alfonso; Carola, Valeria (Journal of affective disorders, 2020)
•Biomarkers and early-life parental care were assessed to identify subgroups of Major Depression Disorder (MDD) patients.•TOLLIP, VEGF-a, and global DNA methylation were differentially expressed between MDD patients and healthy subjects.•SIRT1 differences were modulated by quality of early-life parental care.•SIRT1 and miR-34a levels were correlated with MDD symptoms in low-care patients. The syndromic diagnosis of major depressive disorder (MDD) is associated with individual differences in prognosis, course, treatment response, and outcome. There is evidence that patients with a history to adverse childhood experiences (ACEs) may belong to a distinct clinical subgroup. The combination of data on ACEs and blood biomarkers could allow the identification of diagnostic MDD subgroups. We selected several blood markers (global DNA methylation, and VEGF-a, TOLLIP, SIRT1, miR-34a genes) among factors that contribute to the pathogenetic mechanisms of MDD. We examined their level in 37 MDD patients and 30 healthy subjects. ACEs were measured by the Parental Bonding Instrument and the Childhood Trauma Questionnaire. We found significant differences between patients and healthy subjects in three biomarkers (TOLLIP, VEGF-a, and global DNA methylation), independently from the confounding effect of parental care received. By contrast, SIRT1 differences were modulated by quality of parental care. The lowest levels of SIRT1 were recorded in patients with active symptoms and low maternal/paternal care. miR-34a and SIRT1 levels were associated with MDD symptoms especially in early-life stressed patients. Small sample size, no information on personality comorbidity and suicidal history, cross-sectional definition of remission, and lack of follow-up. Our findings suggest that the levels of global DNA methylation, TOLLIP, and VEGF-a reflect pathophysiological changes associated with MDD that are independent from the long-term effects of low parental care. This study also suggests that SIRT1 may be an additional variable distinguishing the ecophenotype that includes MDD patients with exposure to ACEs.